Lies, slander, and obscenity in medieval English literature : pastoral rhetoric and the deviant speaker - Craun, Edwin D. (Cambridge studies in medieval literature, 1997)
Drawing on manuscript sources, this book examines how the medieval clergy developed the authority and persuasive force to attempt to govern the day-to-day speech of Western Christians. It shows how attempts were made to portray some political, social and private speech as deviant and destructive, labelling it lying, slander, blasphemy and other Sins of the Tongue. It explores, for the first time, how Chaucer, Langland, Gower and the 'Patience' poet use the different strains of this pastoral discourse not only to expose the destructive power of speech in political and social life but also to judge clerical claims to authority and efficacy in formulating and applying codes of speech.